Психофеноменологический профиль как фактор и предиктор персонализации системы психотерапии = Psychophenomenological profile as a factor and predictor of personalization of psychotherapy system - Zaseda, Yu. I.; Gorodokin, A. D. (Journal of Education, Health and Sport, 2015)
Zaseda Yu. I., Gorodokin A. D. Психофеноменологический профиль как фактор и предиктор персонализации системы психотерапии = Psychophenomenological profile as a factor and predictor of personalization of psychotherapy system. Journal of Education, Health and Sport. 2015;5(9):191-208. ISSN 2391-8306. DOI10.5281/zenodo.30529 http://dx.doi.org/10.5281/zenodo.30529 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A191-208 https://pbn.nauka.gov.pl/works/619862 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 29.08.2015. ПСИХОФЕНОМЕНОЛОГИЧЕСКИЙ ПРОФИЛЬ КАК ФАКТОР И ПРЕДИКТОР ПЕРСОНАЛИЗАЦИИ СИСТЕМЫ ПСИХОТЕРАПИИ PSYCHOPHENOMENOLOGICAL PROFILE AS A FACTOR AND PREDICTOR OF PERSONALIZATION OF PSYCHOTHERAPY SYSTEM 1Ю. И. Заседа, 2А. Д. Городокин 1Yu. I. Zaseda, 2A. D. Gorodokin 1Харьковская академия последипломного образования МОЗ Украины 2Запорожский государственный медицинский университет МОЗ Украины 1Kharkiv Academy of Postgraduate Education 2Zaporozhye State Medical University Abstract In order to form a methodical selection protocol of individually-congruent method of psychotherapy based on psychophenomenological profile as a factor and predictor of personalization of psychotherapy system 400 patients suffering from various somatoform and psychosomatic disorders were examined, using clinical- psychophenomenological, psycho-diagnostic, clinical-psychopathological and statistical methods, and as methods of synthesis and analysis. The study was formed concept of using priority form of psychotherapy for patients united by a common pathonosology based on the direction and extent nosospecific pathopersonological transformation. Keywords: psychotherapy, individually-congruent method, psychophenomenological profile, methodical selection. Реферат С целью формирования протокола методической селекции индивидуально-конгруэнтного метода психотерапии на основе психофеноменологического профиля как фактора и предиктора персонализации системы психотерапии было обследовано 400 пациентов, страдающих различными соматоформными и психосоматическими расстройствами, с помощью клинико-психофеноменологического, психодиагностического, клинико-психопатологического и статистического методов, а также методов синтеза и анализа. В результате исследования была сформирована концепция применения приоритетных в отношении пациентов, объединённых единой патонозологичесей формой, методов психотерапии с учетом направления и степени нозоспецифической патоперсонологической трансформации. Ключевые слова: психотерапия, индивидуально-конгруэнтный метод, психофеноменологический профиль, методическая селекция.